Pushing the envelope: a treat and repair strategy for patients with advanced pulmonary hypertension associated with congenital heart disease. (August 2017) - Kameny, Rebecca Johnson; Colglazier, Elizabeth; Nawaytou, Hythem; Moore, Phillip; Reddy, V. Mohan; Teitel, David; Fineman, Jeffrey R.
Pulmonary arterial hypertension (PAH) is a frequent complication of congenital heart disease as a consequence of altered pulmonary hemodynamics with increased pulmonary blood flow and pressure. The development of pulmonary vascular disease (PVD) in this patient population is an important concern in determining operative strategy. Early, definitive surgical repair, when possible, is the best therapy to prevent and treat PVD. However, this is not possible in some patients because they either presented late, after the development of PVD, or they have complex lesions not amenable to one-step surgical correction, including patients with single ventricle physiology, who have a continuing risk of developing PVD. These patients represent an important, high-risk subgroup and many have been considered inoperable. We present a case series of two patients with complex congenital heart disease and advanced PVD who successfully underwent a treat and repair strategy with aggressive PAH therapies before surgical correction. Both patients had normalization of pulmonary vascular resistance prior to surgical correction. Caution is warranted in applying this strategy broadly and long-term follow-up for these patients is crucial. However, this treat and repair strategy may allow for favorable outcomes among some patients who previously had no therapeutic options.